The Effects of AI Anthropomorphism and Service Recovery on Perceived Fairness, Post Recovery Trust, and Recovery Satisfaction in Chinese E-Commerce - LIU, YU; Akkawanitcha, Chuanchuen (RATANABUTH JOURNAL, 2026)
Artificial Intelligence (AI) has become a key component of customer service in e-commerce, particularly in handling service failures and recovery processes. However, the mechanisms through which AI-assisted service recovery influences consumers’ perceptions and post-recovery outcomes remain insufficiently understood. This study examines the effects of AI anthropomorphism and service recovery on perceived fairness, and investigates how perceived fairness subsequently influences post-recovery trust and recovery satisfaction in Chinese e-commerce. Data were collected from 400 users of major Chinese e-commerce platforms using a structured questionnaire and analyzed through descriptive statistics, Pearson correlation, and multiple regression analysis. Results indicate that both AI anthropomorphism and service recovery significantly influence perceived fairness, together explaining 44.7% of its variance. Perceived fairness significantly affects post-recovery trust (Adjusted R² = 0.461) and recovery satisfaction (Adjusted R² = 0.504), with interactional fairness emerging as the most influential dimension. In AI-mediated service encounters, interactional fairness, which reflects consumers’ perceptions of respectful, sincere, and empathetic treatment, proves more influential than distributive or procedural fairness. This occurs because human-like interaction quality is particularly salient when consumers evaluate whether an AI system genuinely cares rather than merely processes complaints. This study extends the Stimulus-Organism-Response (S-O-R) framework and offers practical implications for e-commerce platforms. Findings suggest that AI customer service systems should incorporate calibrated empathy through emotionally responsive language, sincere acknowledgment of concerns, and personalized interactional cues to strengthen interactional fairness perceptions and enhance post-recovery trust and satisfaction.